Genetic diversity for mycorrhizal symbiosis and phosphate transporters in rice - Jeong, Kwanho; Mattes, Nicolas; Catausan, Sheryl; Chin, Joong Hyoun; Paszkowski, Uta; Heuer, Sigrid (Wiley, 2015)
Phosphorus (P) is a major plant nutrient and developing crops with higher P‐use efficiency is an important breeding goal. In this context we have conducted a comparative study of irrigated and rainfed rice varieties to assess genotypic differences in colonization with arbuscular mycorrhizal (AM) fungi and expression of different P transporter genes. Plants were grown in three different soil samples from a rice farm in the Philippines. The data show that AM symbiosis in all varieties was established after 4 weeks of growth under aerobic conditions and that, in soil derived from a rice paddy, natural AM populations recovered within 6 weeks. The analysis of AM marker genes (AM1, AM3, AM14) and P transporter genes for the direct Pi uptake (PT2, PT6) and AM‐mediated pathway (PT11, PT13) were largely in agreement with the observed root AM colonization providing a useful tool for diversity studies. Interestingly, delayed AM colonization was observed in the aus‐type rice varieties which might be due to their different root structure and might confer an advantage for weed competition in the field. The data further showed that P‐starvation induced root growth and expression of the high‐affinity P transporter PT6 was highest in the irrigated variety IR66 which also maintained grain yield under P‐deficient field conditions.